Quasilinearization Technique for -Laplacian Type Equations - Inara Yermachenko; Felix Sadyrbaev (International Journal of Mathematics and Mathematical Sciences)
An equation is considered together with the boundary conditions , . This problem under appropriate conditions can be reduced to quasilinear problem for two-dimensional differential system. The conditions for existence of multiple solutions to the original problem are obtained by multiply applying the quasilinearization technique.